2011
DOI: 10.4088/jcp.09m05694oli
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Stimuli on Affect in Persons With Dementia

Abstract: Objective To examine how presentation of different stimuli impacts affect in nursing home residents with dementia. Method Participants were 193 residents aged 60 to 101 years from 7 Maryland nursing homes who had a diagnosis of dementia (derived from the medical chart or obtained from the attending physician). Cognitive functioning was assessed via the Mini-Mental State Examination (MMSE), and data pertaining to activities of daily living were obtained through the Minimum Data Set. Affect was assessed using … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
42
0
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 58 publications
(46 citation statements)
references
References 40 publications
3
42
0
1
Order By: Relevance
“…Studies which have used questionnaires to assess associations with mood indicate that depressive symptoms of PwD living in long-term care facilities are associated with negative outcomes such as a decreased QoL, worse physical health, a decreased ability to perform activities of daily living, a lack of social support, pain, loneliness, and negative life events (Barca, Engedal, Laks, & Selbaek, 2010;Beerens et al, 2013;Jongenelis et al, 2004). Studies which used real-time observational assessments indicate that negative affect was associated with the presence of agitated behaviour (Cohen-Mansfield, Dakheel-Ali, Jensen, Marx, & Thein, 2012) and positive affect is associated with social stimulation and recreational activities (Cohen-Mansfield, Marx, Thein, & Dakheel-Ali, 2011;Schreiner, Yamamoto, & Shiotani, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…Studies which have used questionnaires to assess associations with mood indicate that depressive symptoms of PwD living in long-term care facilities are associated with negative outcomes such as a decreased QoL, worse physical health, a decreased ability to perform activities of daily living, a lack of social support, pain, loneliness, and negative life events (Barca, Engedal, Laks, & Selbaek, 2010;Beerens et al, 2013;Jongenelis et al, 2004). Studies which used real-time observational assessments indicate that negative affect was associated with the presence of agitated behaviour (Cohen-Mansfield, Dakheel-Ali, Jensen, Marx, & Thein, 2012) and positive affect is associated with social stimulation and recreational activities (Cohen-Mansfield, Marx, Thein, & Dakheel-Ali, 2011;Schreiner, Yamamoto, & Shiotani, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…These results are of particular interest, as antidepressants seem to have little or no effect in this population (Nelson and Devanand, ; Banerjee et al ., ). As the exercise per se did not seem to reduce depressive symptoms in the present study, it suggests that maybe the social contacts mediated in both group activities could be a part of the explanations why positive effects were found in participants with high levels of depressive symptoms (Lenze et al ., ; Yang, ; Cohen‐Mansfield et al ., ). However, as the exercise and control interventions were not compared with usual care in the present study, we cannot disregard the possibility that the observed effects reflect the natural course of depressive symptoms in this group.…”
Section: Discussionmentioning
confidence: 97%
“…Uit onderzoek blijkt dat het aanbieden van verschillende (sociale) activiteiten kan leiden tot een verbetering van het algeheel functioneren, vooral een toename van interesse en plezier [13]. Samen met de activiteitenbegeleidster is een individueel activiteitenaanbod opgesteld bestaande uit lichaamsbeweging, cognitieve activiteiten, ADL en zingeving [9].…”
Section: Diagnose En Behandelingunclassified